Morphologic study of patent ductus arteriosus based on computed tomography data in 25 dogs - Umh, Heesung; Youp, Kyoung-a; Lee, Jeongmin; Seo, Daeyun; Lim, Seongsoo; Namgoong, Beomkwan; Choe, Ahreum; Hong, Hyeajeong; Lee, Nanju; Kim, Isong; Yoon, Junghee; Choi, Jihye; et al. (Frontiers in Veterinary Science, 2024)
IntroductionThe objective of this study is to analyze the morphology and measurement dimensions of patent ductus arteriosus (PDA) based on computed tomography images.MethodsThe present study retrospectively evaluated computed tomography angiography data from 25 client-owned dogs diagnosed with PDA. PDA was reconstructed based on the central axis and the minimum diameter, ampulla diameter, angle, ampulla cross-section area, and length values were measured at specific measurement sites. Additionally, the minimum diameter ratio, ampulla diameter ratio, ampulla cross-section diameter, and ampulla cross-section diameter/ampulla diameter ratio values were calculated based on direct measurement values.Results and discussionThe morphology of PDA was distributed as follows: 48% Type IIA, 20% Type IIB, and 32% Type III. A significant correlation was observed between the minimal diameter sagittal and transverse and the ampulla diameter sagittal and transverse, body weight, and angle (descending aorta to PDA). A significant association was observed between ampulla diameter (in both the sagittal and transverse planes) and body weight. The minimal diameter ratio did not demonstrate a significant correlation with the ampulla diameter, body weight, angle and length. However, the ampulla diameter ratio exhibited a significant correlation with the length of the PDA and the angle (descending aorta to PDA). The minimal diameter ratio displayed results that were more closely approximated by a circle, whereas the ampulla diameter ratio showed results that were relatively oval. The ampulla cross-section diameter values differed by an average of 14% from the previously used reference length, ampulla diameter sagittal.ConclusionThe computed tomography image demonstrated the distinctive cross-sectional configuration of the PDA, which could potentially facilitate advanced pre-procedural planning or the creation of novel occluding devices in the future.